Effect of Seaweed Liquid Fertilizers on Productivity of vigna radiata (L).Wiliczek - Venkata Rao P.; Reddy A. S.; Koteswara Rao Y. (International Journal of Research in Chemistry and Environment (IJRCE), 2015)
A field experiment was conducted at Regional Agricultural Research Station, Lam, Guntur during rabi seasons of 2012-2013 and 2013-2014 to study the effects of seaweed liquid fertilizers on growth and yield of greengram on deep black clay loam soils. The foliar application was done twice at different concentrations (0, 2.5, 5.0,7.5,10.0 and 15.0 % v/v) of seaweed liquid fertilizers (namely Kappaphycus and Gracelaria). Control plot was sprayed with water. Foliar application of either kappaphycus and gracilaria @10 % sap at flowering stage and pod development stage resulted in increased plant height, branches per plant, number of pods per plant, test weight (100 grain) and grain yield (19.3% and 25.4% respectively) over the control. The presence of micro and macro nutrients, vitamins, growth hormones and other constituents in the seaweed extract might be very much useful to the crops but their level should be appropriate to enhance growth and productivity. It may be concluded that liquid seaweed extracts could serve as cost effective eco-friendly product for sustainable agriculture.